PERTANGGUNGJAWABAN PIDANA TERHADAP PENGGUNAAN BILYET GIRO SEBAGAI ALAT PEMBAYARAN YANG KEWAJIBANNYA TIDAK DAPAT TERLAKSANA - , Farman ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Macroeconomic developments make a significant impacts to several aspect as the political, legality, industrial, social, and cultural of a country. Logical consequence ( adequacy ) of a country's economic development is the increasing flow of payment in commercial transactions. Beginning from a small value of sale and purchase transactions such as public marketing, until the fantastic value transaction of sale. Government has issued a terms of payment system to support the dinamical of payment system, by issuing a commercial paper / negotiable instrument as noncash payment instrument. The use of commercial paper as a noncash payment instrument on national or international business practices had proven demand even though sometimes it couses some risk of disadvantages. Therefore, the use of commercial papaer as a noncash payment instrument proved effectiveness in the flow of trade. The government should give more attention to the risk of disadvantages in the use of commercial paper. Increased risk of disadvantages led to declining interest in the business to use a commercial paper as noncash payment instrument which implies decreased of national income.This research focuses on the normative legality research through the library research. Bilyet Giro Publishing is a handeling legality, that giving rise to legality consequences. The legality consequences arising from an act or deed of someone always implications for the interests of others, if the legality consequences that arise not harming the others, then the interests of the law will not be violated. Otherwise, there will be legality consequences such as sanctions, both civil or criminal law if an act or deed ( handeling ) giving rise to harm. it's depending on what had been done and what the losses incurred or failures. Till this moment, the empty of bilyetgiroâs position as a criminal acts (stafbaarfeit) still debatable, both in theorical and practical. Talking about an act of responsibility, as well as talking about the responsibility system that has been adopted in the legal system in Indonesia. The concept of \"Responsibility\" is a word or term used in criminal law shutter, but responsibility of civil commonly called âAccountabilityâ which has the same meaning, but have different characteristics.